THE KNOWLEDGE AND ATTITUDES OF ADOLESCENTS IN FACING MENSTRUAL PROBLEMS IN PEMALANG IN 2024 - Elqy Mei Zumaro (The Shine Cahaya Dunia Kebidanan, 2024)
Background: Dysmenorrhea refers to abdominal pain that may radiate to the lower back. Secondary dysmenorrhea is hip discomfort due to certain conditions or diseases. In most cases, women report symptoms such as abdominal pain or cramps before menstruation, which usually lasts 2-3 days and begins a few days before menstruation. The goal of this research is to investigate how knowledge and skills improve performance when dealing with dismenore. Method: This research uses an analytical survey method with a quantitative approach and cross-sectional design. The population and sample consisted of all teenagers who visited Posyandu Anggrek in Asemdoyong Village in June 2024, with a total of 91 respondents. Results: From the research results, it was found that 81 respondents (89.0%) had good knowledge, while 10 respondents (11.0%) had poor knowledge. Of the total respondents, 56 people (61.5%) showed a positive attitude, while 35 people (38.5%) showed a negative attitude. In addition, 26 respondents (28.6%) showed good behavior, while 65 respondents (71.4%) showed bad behavior. Data analysis revealed that the knowledge variable did not correlate with adolescent behavior in dealing with dysmenorrhea (P = 0.052), while the attitude variable showed a significant relationship (P = 0.010).